Innovation in Action: Exploring the Effectiveness of a MOOC in Teacher Education - Ansari, Shama P.; Biswal, Ashutosh (Voices of Teachers and Teacher Educators, 2024)
MOOCs are Massive Open Online Courses that are open and accessible to those with a stable internet connection. There is no kind of biasness concerning caste, creed, gender, etc. for its enrolment and registration which makes learning through MOOC inclusive. Learners can select any course of their choice irrespective of their previous background. The courses are also free in most cases and there are provisions for financial assistance in the case of paid courses. MOOCs have discussion spaces where students can talk with other learners from different regions and of differing backgrounds. The course provides students with self-paced learning and learning at their own convenient time. People who are doing a job and lack time to study in physical mode can enroll in such courses and get the benefits of online learning. Though MOOC has gained momentum worldwide, MOOCs in India are in a nascent stage. The Teacher Education programs should prepare students to use new technology in the classroom to meet the demands and aspirations of students in the twentyfirst century. To fulfil these educational demands of students, we require teachers who know how to deliver knowledge and who truly care about students and their future success. The researchers in the present study developed a MOOC for pre-service teacher educators and studied its effectiveness with the help of an achievement test prepared and validated by the researchers. The developed MOOC enabled students to get acquainted with a new method of learning, compelling them to use various authentic open educational resources available on the online platform, enabling self-paced and flexible learning. The analysis indicates that MOOC was found to be effective in enhancing pre-service teacher educators’ achievement. The findings support the idea that pre-service teacher educators need to be trained for developing Massive Open Online Courses in their respective subjects by utilizing the various free open-source software available online.